Hybridized and Complementary Comparative Analysis of Dissolved Gases in a Power Transformer. Issue 1 (1st March 2022) - Kaur, Kulraj; Bhalla, Deepika; Singh, Jashandeep
Abstract: Power transformer is considered important equipment both in the transmission and distribution zone of electric power. Safety of power system elements plays a crucial role for enhancing its reliability. Transformer being a major component plays a much vital role and needs to be monitored and maintained at a regular basis. Transformer oil helps in performing the functions of insulation, cooling and helps extinguish arcs. Transformer oil also dissolves the gases which get generated by the degradation of oil, presence of moisture and gas from insulation deterioration of cellulose, gases and moisture from the surrounding, to which the oil is exposed. The dissolved gas present in an oil sample can be helpful in determining the nature of a fault which can vary according to gas types and its concentrations. DGA (Dissolved Gas Analysis) have been used as a suitable tool in enabling the reliability of the system and safety of the transformer for a long time. An analysis of Dissolved gases in oil is analytical method and have been used and interpreted differently by different methods and users. DGA methods using ratios, gas concentration and graphical methods have been presented in this work. The tools use mix of fuzzy based analysis, MATLAB. The basic motivation of the work is to create a platform for DGA analysis so as to provide early and easy detection and diagnosis of Transformer Failures.